Photofermentative production of hydrogen and poly-β-hydroxybutyrate from dark fermentation products. (March 2017) - Luongo, Vincenzo; Ghimire, Anish; Frunzo, Luigi; Fabbricino, Massimiliano; d'Antonio, Giuseppe; Pirozzi, Francesco; Esposito, Giovanni
Highlights: Photofermentative treatment of a dark fermentation effluent is investigated. Performances of a R. sphaeroides and a mixed PNSB culture are compared. The mixed culture results more efficient in H2 production (233.8 N mL H2 g COD −1 ). The pure culture shows a higher PHB productivity (155 mg PHB g COD −1 ). High soluble COD removal from DFE is achieved (>80%). Abstract: The aim of this work is to investigate the hydrogen and poly-β-hydroxybutyrate (PHB) production during the photofermentative treatment of the effluent from a dark fermentation reactor fed with the organic fraction of municipal solid waste. Two different inocula, an adapted culture of Rhodobacter sphaeroides AV1b and a mixed consortium of purple non sulphur bacteria have been investigated under the same operational conditions. Different hydrogen productivities of 364 and 559 N mL H2 L −1 were observed for the Rhodobacter sphaeroides and the mixed culture consortium tests, respectively: the consortium of PNSB resulted 1.5-fold more productive than the pure culture. On the other hand, Rhodobacter sphaeroides culture showed a higher PHB productivity (155 mg PHB g COD −1 ) than the mixed culture (55 mg PHB g COD −1 ). In all the tests, the concomitant H2 and PHB production was associated to a dissolved COD removal higher than 80%.